ISOLATION AND MOLECULAR CHARACTERIZATION OF SHIGA TOXIN PRODUCING E. COLI O157 - K. A. Shahzad; K. Muhammad; A. A. Sheikh; T. Yaqub; M. Rabbani; T. Hussain; A. A. Anjum; M. Anees (Journal of Animal and Plant Sciences, 2013)
Escherichia coli (E. coli) is normal inhabitant of all domestic animals and human beings. Its Sorbitol-non fermenting (SNF) biotype was detected in dung of buffalo (92 %), cattle (84 %), sheep (52 %) and goat (56 %). However, E. coli (SNF) was not detected in droppings of rural chickens, feces of donkeys and fresh aseptically collected milk and beef samples, whereas, the E. coli was detected in 96 percent market raw milk and 82 percent samples from beef shops. Eighty percent milk and 53 percent beef samples contained SNF isolates of E. coli. All isolates of SNF E. coli showing green metallic sheen on eosin methylene blue (EMB) agar were further characterized using polymerase chain reaction (PCR). The isolated DNA of 100 samples when amplified using universal, Stx1, Stx2 and O157 specific primers confirmed that 82 percent samples were positive for universal primers, 50 percent for O157, 60 percent for Stx1 and 51 percent for Stx2. It is concluded that E. coli O157 is normal inhabitant of intestinal tract of domestic ruminants and presumably animal feces are acting as main source of contamination of raw milk and beef.
Keywords: Sorbitol; Eosin Methylene Blue (EMB) agar; E. coli O157; PCR; Buffalo; Sorbitol Non Fermenters